The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.cell.2019.08.052
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Proteogenomic Characterization of HBV-Related Hepatocellular Carcinoma

Abstract: Highlights d Proteomic subgroups stratify patient survival and allocate specific treatments d Alterations of the liver-specific proteome and metabolism in HCC are identified d Multi-omics profile of key signaling and metabolic pathways in HCC is depicted d CTNNB1 mutation-associated ALDOA phosphorylation promotes HCC cell proliferation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
503
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 668 publications
(582 citation statements)
references
References 83 publications
33
503
1
2
Order By: Relevance
“…Globally, liver cancer is the fourth leading cause of cancer-related deaths, with the sixth highest incidence (1). HCC accounts for about 80% of all cases of primary liver cancer, most of which occur in patients with chronic diseases such as hepatitis B virus (HBV), hepatitis C virus (HCV) and alcoholism (25,26). The increase in deaths caused by HCC is a growing concern.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, liver cancer is the fourth leading cause of cancer-related deaths, with the sixth highest incidence (1). HCC accounts for about 80% of all cases of primary liver cancer, most of which occur in patients with chronic diseases such as hepatitis B virus (HBV), hepatitis C virus (HCV) and alcoholism (25,26). The increase in deaths caused by HCC is a growing concern.…”
Section: Discussionmentioning
confidence: 99%
“…BRC1 was reported to be a potential prognostic biomarker in various tumors, such as adrenocortical carcinoma (Xu W. H. et al, 2019) and non-muscle invasive bladder cancer (Shi et al, 2019). IGF2BP3 is a prognostic marker of poor outcome for colorectal cancer , glioma (Gao Q. et al, 2019;Zhang et al, 2019), and papillary renal cell carcinoma . The overexpression of KIF2C has been significantly associated with poor prognosis of HCC (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To explore effective biomarkers for HCC diagnosis at early stage, multiple kinds of omics studies have been performed with samples from HCC patients or HCC cell lines, such as genomics, transcriptomics, proteomics, metabolomics, and so on. These omics studies provided huge number of molecules including circulating tumor DNA (ctDNA), circulating miRNAs, proteins, and metabolites as biomarker candidates for clinical HCC diagnosis (Tang et al, 2016;Zhou et al, 2011;Dittharot et al, 2018;Gao et al, 2019). Based on the data from omics studies, several effective biomarkers were identified and validated in clinical samples from HCC patients, among which AFP was the most widely used protein biomarker for early diagnosis of HCC (Marrero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%